Fast tract: Pengaruh Dukungan Sosial dan Dukungan Psikologis Terhadap Peningkatan Kualitas Hidup Pasien Kanker - Darmajayanti, Febry; Nuraini, Tuti; Waluyo, Agung; Gayatri, Dewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
ABSTRACT Introduction: Cancer is one of the most challenging and high-risk diseases, which not only affects the physical health of patients but also their mental and emotional health. Objective: to explore the effect of social support and psychological support on improving the quality of life of cancer patients. Method: This Article used a systematic review method compiled based on the Preferred Referring Items for Systematic Reviews and Meta-Analyzes (PRISMA). The databases used include ProQuest, Jstor, Science Direct, Pubmed. Results: 11 articles that met the inclusion criteria were then analyzed and critiqued using the CASP instrument. Conclusion: social support and psychological support have a significant impact on improving the quality of life of cancer patients. Consistent social support from the surrounding environment plays an important role in providing a sense of security and reducing feelings of isolation and improving emotional well-being. In addition, psychological support through professional interventions not only reduces symptoms of anxiety and depression but also increases life expectancy and mental resilience of patients. Therefore, the integration of these two types of support in cancer patient care is highly recommended to maximize the quality of life of patients. Further research is needed to identify more specific and effective intervention methods in diverse contexts.Keywords: social support, psychological support, cancer, quality of life